Conductive paste and paste cured product

The conductive paste, with a specific metal content range and metal-coated resin particles, addresses the challenge of achieving high conductivity and low elastic modulus in conductive pastes, resulting in a hardened paste suitable for electronic device applications.

JP2025056455APending Publication Date: 2025-04-08MITSUBISHI MATERIALS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023165938
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Conductive pastes struggle to achieve both high conductivity and low elastic modulus, leading to challenges in forming effective bonding layers and conductive members in electronic devices.

Method used

A conductive paste with a metal content within the range of 11% to 19% by volume, combined with a binder resin and metal-coated resin particles, is used to create a hardened paste with a volume resistivity of 5×10^-3 Ω·cm or less and an elastic modulus of 300 MPa or less.

Benefits of technology

The resulting hardened paste exhibits high conductivity and low elastic modulus, making it suitable for use as a conductive bonding layer or conductive member in electronic devices, while also reducing thermal stress and frequency fluctuations in quartz resonators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056455000002
    Figure 2025056455000002
  • Figure 2025056455000003
    Figure 2025056455000003
  • Figure 2025056455000001
    Figure 2025056455000001
Patent Text Reader

Abstract

To provide a conductive paste capable of forming a paste cured product achieving both high conductivity and low elastic modulus, and to provide a paste cured product.SOLUTION: The conductive paste contains a conductive filler containing a metal, and a binder resin. The content of the metal contained in a solid component is within the range of 11 vol.% or more and 19 vol.% or less. A paste cured product obtained by firing the conductive paste under the condition of being held at 150°C for one hour has a volume resistivity of 5×10-3 Ω cm or less. The cured product preferably has an elastic modulus of 300 MPa or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive adhesive layer, a conductive paste for forming electrodes and wiring, and a hardened paste. [Background technology]

[0002] For example, various devices such as LEDs and power modules have a structure in which electronic components such as semiconductor elements are bonded onto a circuit layer made of a metal material. When bonding an electronic component and a circuit layer, a conductive paste may be used, as disclosed in, for example, Patent Document 1. A conductive bonding layer is formed by applying the conductive paste to the bonding surfaces of the electronic component and the circuit layer and curing it, which bonds the electronic component and the circuit layer and makes it possible to electrically connect them.

[0003] In addition, in various devices, conductive members such as circuit layers, electrodes, and wiring are formed in a predetermined pattern. The conductive members are sometimes formed using the above-mentioned conductive paste. That is, the conductive paste is applied in a pattern on a substrate and cured, thereby making it possible to form a conductive member having a predetermined pattern.

[0004] Here, the above-mentioned conductive adhesive layer, conductive member, and the like are required to have excellent conductivity and a sufficiently low elastic modulus to relieve thermal stress when subjected to a thermal cycle. Therefore, Patent Document 1 proposes a technology that contains a binder resin and a conductive metal filler, and the binder resin is rubber-modified or has a rubber component added thereto, thereby keeping the elastic modulus low. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-238798 A Summary of the Invention [Problem to be solved by the invention]

[0006] In the conductive paste containing a conductive filler and a binder resin, it is possible to reduce the content of the conductive filler in order to keep the elastic modulus low. However, when the content of the conductive filler is reduced, there is a risk that the conductivity will decrease. Even in the technology described in Patent Document 1, it was necessary to reduce the content of the conductive filler in order to sufficiently reduce the elastic modulus. As described above, with conventional conductive pastes, it has been difficult to form a paste cured product that has both high electrical conductivity and a low elastic modulus.

[0007] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide a conductive paste capable of forming a paste-cured product that has both high electrical conductivity and a low elastic modulus, and a paste-cured product. [Means for solving the problem]

[0008] In order to solve the above problems, the conductive paste according to the first aspect of the present invention includes a conductive filler containing a metal and a binder resin, the content of the metal contained in the solid component is within a range of 11% by volume to 19% by volume, and the volume resistivity of a paste cured product obtained by firing at 150° C. for 1 hour is 5×10 -3 It is characterized by a resistance of less than Ω·cm.

[0009] According to the conductive paste of the first aspect of the present invention, the content of the metal contained in the solid component is within the range of 11 volume % or more and 19 volume % or less, and since the metal content is kept relatively low, it is possible to keep the elastic modulus of the cured product low. Furthermore, the volume resistivity of the paste cured product obtained by firing at 150°C for 1 hour is 5×10 -3Since the electrical resistance is set to Ω·cm or less, it is possible to form a paste cured product that has both high electrical conductivity and a low elastic modulus.

[0010] The conductive paste of the second aspect of the present invention is the conductive paste of the first aspect of the present invention, characterized in that the cured product has an elastic modulus of 300 MPa or less.

[0011] According to the conductive paste of aspect 2 of the present invention, the elastic modulus of the cured product is set to 300 MPa or less, so that it is possible to reliably keep the elastic modulus of the cured product low.

[0012] The conductive paste of aspect 3 of the present invention is the conductive paste of aspect 1 or aspect 2 of the present invention, characterized in that the elastic modulus of the binder resin is within the range of 0.1 MPa or more and 290 MPa or less.

[0013] According to the conductive paste of aspect 3 of the present invention, the elastic modulus of the binder resin is within the range of 0.1 MPa or more and 290 MPa or less, so that it is possible to reliably keep the elastic modulus of the cured product low.

[0014] The conductive paste of aspect 4 of the present invention is characterized in that, in the conductive paste of any one of aspects 1 to 3 of the present invention, the conductive filler includes metal-coated resin particles in which the surface of resin particles is coated with a metal.

[0015] According to the conductive paste of aspect 4 of the present invention, the conductive filler contains metal-coated resin particles in which the surfaces of resin particles are coated with a metal, so that even if the content of the metal contained in the solid component is reduced, it is possible to reliably improve the conductivity of the cured product.

[0016] The conductive paste of aspect 5 of the present invention is characterized in that, in the conductive paste of any one of aspects 1 to 4 of the present invention, the content of the conductive filler contained in the solid component is in the range of 44 volume % or more and 59 volume % or less.

[0017] According to the conductive paste of aspect 5 of the present invention, the conductive filler contains metal-coated resin particles in which the surfaces of resin particles are coated with a metal, so that even if the content of the metal contained in the solid component is reduced, it is possible to reliably improve the conductivity of the cured product.

[0018] The conductive paste of the sixth aspect of the present invention is the conductive paste of any one of the first to fifth aspects of the present invention, characterized in that it is used as a conductive adhesive for a quartz crystal unit.

[0019] Quartz crystal units are used in various electronic control devices, computers, and other electronic components. A quartz crystal unit is a device in which a quartz crystal piece is sandwiched between electrodes made of gold or silver, and a signal current is passed through it to extract vibrations. In the manufacture of quartz crystal units, conductive adhesives are often used to hold the quartz crystal piece in place. When manufacturing a quartz crystal oscillator, if a quartz crystal piece is attached to an electrode substrate such as a gold electrode, the conductive paste of the present invention can be used as a conductive adhesive. Since the elastic modulus of the cured paste is low, it is possible to reduce fluctuations in the frequency of the quartz crystal oscillator even if the electrode area of ​​the electrode is reduced (made smaller).

[0020] The cured paste of the seventh aspect of the present invention is a cured conductive paste according to any one of the first to sixth aspects of the present invention, and has a volume resistivity of 5×10 -3 It is characterized by a resistivity of Ω·cm or less and an elastic modulus of 300 MPa or less.

[0021] According to the seventh aspect of the present invention, the cured paste of the conductive paste of any one of the first to sixth aspects of the present invention has a volume resistivity of 5×10 -3 With a resistivity of Ω·cm or less and an elastic modulus of 300 MPa or less, it has high electrical conductivity and a low elastic modulus, and is particularly suitable as a conductive bonding layer or conductive member. Effect of the Invention

[0022] According to the present invention, it is possible to provide a conductive paste capable of forming a cured paste that has both high electrical conductivity and low elastic modulus, and the cured paste. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is an explanatory diagram of a semiconductor device using a hardened paste according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram showing an example of a conductive filler contained in a conductive paste according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, a conductive paste and a cured paste according to embodiments of the present invention will be described with reference to the drawings.

[0025] FIG. 1 shows a semiconductor device using a cured product of the conductive paste according to this embodiment. 1, this semiconductor device 10 has a structure in which a circuit layer 11 of an insulating circuit board and a semiconductor element 12 are bonded via a conductive bonding layer 13. Here, the conductive bonding layer 13 is composed of a cured product of the paste according to this embodiment (a cured product of the conductive paste according to this embodiment).

[0026] Next, the conductive paste of this embodiment used in forming the conductive adhesive layer 13 (cured paste) will be described. The conductive paste of this embodiment contains a conductive filler containing a metal and a binder resin, and the metal content in the solid components (conductive filler and binder resin) is in the range of 11 volume % or more and 19 volume % or less. The conductive paste of this embodiment may contain a solvent and an additive in addition to the conductive filler and binder resin.

[0027] In the conductive paste of the present embodiment, the volume resistivity of the cured product of the conductive paste is 5×10 -3 It is said to be Ω·cm or less. That is, in the conductive paste of this embodiment, the metal content in the solid components is relatively low, within the range of 11 volume % or more and 19 volume % or less, so that it is possible to ensure high conductivity while keeping the elastic modulus of the cured product low. In the conductive paste of this embodiment, the elastic modulus of the cured conductive paste is preferably 300 MPa or less. The elastic modulus of the cured conductive paste is a value measured at 25° C. using a dynamic viscoelasticity measuring device. The hardening conditions for the conductive paste are preferably set appropriately depending on the binder resin, but in this embodiment, the conditions are set to 150° C. and holding for 1 hour.

[0028] In the conductive paste of this embodiment, the elastic modulus of the binder resin is preferably within the range of 0.1 MPa to 290 MPa, and the elastic modulus of the binder resin is a value measured at 25° C. using a dynamic viscoelasticity measuring device. By setting the elastic modulus of the binder resin within the above range, it is possible to keep the elastic modulus of the cured paste sufficiently low.

[0029] In the conductive paste of this embodiment, there is no particular limitation on the metal contained in the conductive filler, but in this embodiment, Ag, which has excellent conductivity, is used.

[0030] In the conductive paste of this embodiment, the conductive filler preferably contains metal coated resin particles 20 having a core-shell structure in which a metal coating film 22 is formed on the surface of a resin particle 21 as shown in FIG. By the conductive filler containing metal-coated resin particles 20 having a core-shell structure, it is possible to make the conductivity of the cured product sufficiently high even when the metal content in the solid component is 11 volume % or more and 19 volume % or less.

[0031] The metal-coated resin particles 20 are produced by forming a metal coating film 22 by metal plating or the like on the surface of a resin particle 21. It is not necessary for the entire resin particle 21 to be covered with the metal coating film 22, and the coverage (area rate) of the metal coating film 22 is preferably 90% or more. The average particle size of the resin particles 21 is preferably in the range of 1 μm to 110 μm, more preferably 1 μm to 50 μm. If the average particle size is less than 1 μm, the surface area of ​​the resin particles becomes large, and it is necessary to increase the amount of silver to obtain the necessary conductivity as a conductive particle. If the average particle size is more than 110 μm, it is likely to be difficult to apply the silver-coated resin particles to a fine pattern. The average thickness of the metal coating film 22 is preferably within the range of 0.01 μm to 0.5 μm. The resin constituting the resin particles 21 is not particularly limited, but in this embodiment, the resin particles 21 are made of acrylic resin or silicone resin.

[0032] When the conductive filler contains metal coated resin particles 20 having a core-shell structure, the content of the metal contained in the solid component is calculated by the following formula. (Metal content in solid components (volume %))=(Volume of metal contained in conductive filler) / {(Volume of metal contained in conductive filler)+(Volume of resin particles in conductive filler)+(Volume of binder resin)}×100

[0033] In the conductive paste of this embodiment, the content of the conductive filler in the solid components (conductive filler and binder resin) is preferably within the range of 11% by volume to 19% by volume.

[0034] In addition, the conductive paste of this embodiment preferably has a viscosity at 25° C. in the range of 1 Pa·s or more and 300 Pa·s or less. In addition, the material of the binder resin, which is a solid component, is not particularly limited, but in this embodiment, it is an epoxy resin. Furthermore, the average particle size of the conductive filler is preferably within the range of 1 μm or more and 110 μm or less.

[0035] The conductive paste of this embodiment is manufactured as follows. First, the conductive filler and the binder resin are weighed out to have a predetermined ratio. When the conductive filler contains metal-coated resin particles 20, the content of metal contained in the solid components (conductive filler and binder resin) is adjusted to be within the range of 11% by volume to 19% by volume, taking into account the core resin particles 21. In addition, a solvent and additives are prepared as necessary. Then, the conductive filler and binder resin, and optionally a solvent and additives, are added and kneaded to produce the conductive paste of this embodiment.

[0036] Next, a method for manufacturing the semiconductor device 10 shown in FIG. 1 will be described. First, the conductive paste of the present embodiment is applied to one or both of the bonding surface of the circuit layer 11 of the insulating circuit board and the bonding surface of the semiconductor element 12. The method for applying the conductive paste is not particularly limited, but for example, a metal mask method, a screen printing method, a dispense method, or the like can be applied.

[0037] Then, the circuit layer 11 and the semiconductor element 12 are laminated with the applied conductive paste therebetween, and the conductive paste is fired. This forms a conductive bonding layer 13 (a hardened paste product in this embodiment) to bond the circuit layer 11 and the semiconductor element 12 together. The baking conditions can be appropriately selected depending on the binder resin, but it is preferable that the baking temperature is within the range of 130° C. to 250° C., and the holding time at the baking temperature is within the range of 0.5 hours to 2.0 hours.

[0038] According to the conductive paste of this embodiment configured as described above, the metal content of the conductive filler contained in the solid components (conductive filler and binder resin) is within the range of 11 volume % or more and 19 volume % or less, and since the metal content is kept relatively low, it is possible to keep the elastic modulus of the cured product low. The volume resistivity of the cured product of the conductive paste of this embodiment is 5×10 -3 Since the electrical resistance is set to Ω·cm or less, it is possible to form a paste cured product that has both high electrical conductivity and a low elastic modulus.

[0039] In this embodiment, when the elastic modulus of the cured product of the conductive paste is 300 MPa or less, the elastic modulus of the cured product is sufficiently low, and the cured product can relieve stress.

[0040] In this embodiment, when the elastic modulus of the binder resin, which is a solid component, is within the range of 0.1 MPa to 290 MPa, it is possible to reliably keep the elastic modulus of the cured product of the conductive paste low.

[0041] In this embodiment, when the conductive filler includes metal-coated resin particles 20 having a core-shell structure in which a metal coating film 22 is formed on the surface of a resin particle 21, it is possible to reliably improve the conductivity of the cured conductive paste even if the content of metal contained in the solid component is reduced.

[0042] In this embodiment, when the content of the conductive filler in the solid components (conductive filler and binder resin) is in the range of 44 volume % or more and 59 volume % or less, it is possible to reliably improve the conductivity of the cured product of the conductive paste even if the content of the metal in the solid components is reduced.

[0043] According to the cured paste of the present embodiment, the volume resistivity of the cured conductive paste of the present embodiment is 5×10 -3Since the resistivity is Ω·cm or less and the elastic modulus is 300 MPa or less, it has high electrical conductivity and a low elastic modulus, and is particularly suitable as the conductive bonding layer 13 .

[0044] Although the embodiment of the present invention has been described above, the present invention is not limited to this, and can be modified as appropriate without departing from the technical concept of the invention. EXAMPLES

[0045] The results of confirmatory experiments conducted to confirm the effectiveness of the present invention will be described below.

[0046] (Example 1 of the present invention) 34 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 5 parts by mass of diethylene glycol dimethyl ether as the solvent were weighed out and mixed using a planetary mixer to produce the conductive paste of Example 1 of the present invention.

[0047] (Example 2 of the present invention) 34 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 6 parts by mass of butyl carbitol as the solvent were weighed out and mixed using a planetary stirrer to produce a conductive paste of Example 2 of the present invention.

[0048] (Example 3 of the present invention) 40 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 7 parts by mass of propylene glycol monomethyl ether acetate as the solvent were weighed out and mixed using a planetary stirrer to produce a conductive paste of Example 3 of the present invention.

[0049] (Example 4 of the present invention) 40 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 8 parts by mass of diethylene glycol dimethyl ether as the solvent were weighed out and mixed using a planetary mixer to produce a conductive paste of Example 4 of the present invention.

[0050] (Example 5 of the invention) 54 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 10 parts by mass of ethyl carbitol acetate as the solvent were weighed out and mixed using a planetary mixer to produce the conductive paste of Example 5 of the present invention.

[0051] (Example 6) 33 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 8 parts by mass of butyl cellosolve acetate as the solvent were weighed out and mixed using a planetary mixer to produce a conductive paste of Example 6 of the present invention.

[0052] (Example 7) 34 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 6 parts by mass of ethylene glycol monoethyl ether acetate as the solvent were weighed out and mixed using a planetary stirrer to produce a conductive paste of Example 7 of the present invention.

[0053] (Example 8) 40 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 10 parts by mass of butyl cellosolve as the solvent were weighed out and mixed using a planetary stirrer to produce a conductive paste of Example 8 of the present invention.

[0054] (Example 9) 54 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 12 parts by mass of butyl cellosolve acetate as the solvent were weighed out and mixed using a planetary mixer to produce the conductive paste of Example 9 of the present invention.

[0055] Comparative Example 1 29 parts by mass of silver-coated resin particles as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 2 parts by mass of ethylene glycol monoethyl ether acetate as the solvent were weighed out and mixed using a planetary mixer to produce the conductive paste of Comparative Example 1.

[0056] Comparative Example 2 67 parts by mass of silver-coated resin particles were weighed out as the conductive filler, 10 parts by mass of thermosetting epoxy resin as the binder resin, and 12 parts by mass of butyl cellosolve acetate as the solvent, and these were mixed using a planetary mixer to produce the conductive paste of Comparative Example 2.

[0057] Comparative Example 3 49 parts by mass of silver powder was weighed out as the conductive filler, 10 parts by mass of thermosetting epoxy resin was weighed out as the binder resin, and 6 parts by mass of propylene glycol monomethyl ether acetate was weighed out as the solvent. These were then mixed using a planetary stirrer to produce the conductive paste of Comparative Example 3.

[0058] Comparative Example 4 92 parts by mass of silver powder was weighed out as the conductive filler, 10 parts by mass of thermosetting epoxy resin was weighed out as the binder resin, and 15 parts by mass of ethyl carbitol acetate was weighed out as the solvent. These were then mixed using a planetary stirrer to produce the conductive paste of Comparative Example 4.

[0059] Comparative Example 5 82 parts by mass of silver powder was weighed out as the conductive filler, 10 parts by mass of thermosetting epoxy resin was weighed out as the binder resin, and 12 parts by mass of diethylene glycol dimethyl ether was weighed out as the solvent, and these were mixed using a planetary mixer to produce the conductive paste of Comparative Example 5.

[0060] The conductive pastes of Examples 1 to 9 of the present invention and Comparative Examples 1 to 5 obtained as described above were evaluated as follows.

[0061] (Elastic modulus of cured product) The obtained conductive paste was printed onto a PTFE substrate using a screen printing method to obtain a width of 5 mm, length of 100 mm, and thickness of 500 μm. The substrate was then placed in a hot air circulating furnace and fired at a temperature of 150° C. for 1 hour. The elastic modulus of the resulting cured product at 25° C. was measured by a tensile test using a dynamic viscoelasticity measuring device (RSA-G2, manufactured by TA Instruments). In Table 1, the elastic modulus of 300 MPa or less is indicated by "◯", and the elastic modulus of more than 300 MPa is indicated by "X".

[0062] (Volume resistivity of cured product) The obtained conductive paste was printed onto a glass substrate using a screen printing method to obtain a width of 10 mm, length of 10 mm, and thickness of 50 μm. The substrate was then placed in a hot air circulating furnace and fired at a temperature of 150°C for 1 hour. The volume resistivity (Ω cm) of the obtained cured product was calculated from the surface resistance measured using a four-terminal four-probe type surface resistivity meter (Loresta GX MCP-T700, manufactured by Nitto Seiko Analytech Co., Ltd.) and the film thickness measured using an optical microscope. In Table 1, the volume resistivity is 5×10 -3 If the volume resistivity is less than 5×10 -3 Cases exceeding Ω·cm are indicated as "×".

[0063] [Table 1]

[0064] In Comparative Example 1, the content of metal in the solid components was 10.6% by volume, and the volume resistivity was high and the electrical conductivity was poor. In Comparative Example 2, the metal content in the solid component was 20.5% by volume, and the elastic modulus was high. In Comparative Example 3, the metal content in the solid component was 33.0% by volume, and the elastic modulus was high. In Comparative Example 4, the metal content in the solid component was 48.0% by volume, and the elastic modulus was high. In Comparative Example 5, the metal content in the solid component was 45.0 volume %, and the elastic modulus was high.

[0065] In contrast, in Examples 1 to 9 of the present invention, the content of the metal in the solid component was in the range of 11% by volume or more and 19% by volume or less, and the elastic modulus of the cured product was sufficiently low. -3 The electrical conductivity was excellent, being less than Ω·cm.

[0066] From the results of the above confirmation experiments, it was confirmed that the present invention can provide a conductive paste capable of forming a paste-cured product that has both high electrical conductivity and low elastic modulus, and a paste-cured product. [Explanation of symbols]

[0067] 13 Conductive adhesive layer (hardened paste) 20 Metal coated resin particles 21 Resin particles 22 Metal coating membrane

Claims

1. The conductive filler contains a metal, and a binder resin, and the content of the metal contained in the solid component is within a range of 11% by volume or more and 19% by volume or less, The volume resistivity of the paste cured product obtained by firing at 150° C. for 1 hour is 5×10 -3 A conductive paste having a resistivity of Ω·cm or less.

2. 2. The conductive paste according to claim 1, wherein the elastic modulus of the cured product is 300 MPa or less.

3. 2. The conductive paste according to claim 1, wherein the elastic modulus of the binder resin is within a range of 0.1 MPa to 290 MPa.

4. 2. The conductive paste according to claim 1, wherein the conductive filler includes metal-coated resin particles in which the surfaces of resin particles are coated with a metal.

5. 2. The conductive paste according to claim 1, wherein the content of the conductive filler in the solid component is within a range of 44% by volume to 59% by volume.

6. 2. The conductive paste according to claim 1, which is used as a conductive adhesive for a quartz crystal oscillator.

7. A cured product of the conductive paste according to any one of claims 1 to 6, having a volume resistivity of 5×10 -3 A paste cured product having a resistivity of Ω·cm or less and an elastic modulus of 300 MPa or less.

Citation Information

Patent Citations

  • Conductive adhesive agent and electrode junction structure and semiconductor package using the same

    JP2012238798A